2005
DOI: 10.1021/ja050265j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Interplay between Long-Range Electron Transfer and Redox Probe Permeation at Self-Assembled Monolayers:  Evidence for Potential-Induced Ion Gating

Abstract: Evidence for the competition between long-range electron transfer across self-assembled monolayers (SAMs) and incorporation of the redox probe into the film is reported for the electroreduction of Ru(NH(3)) at hydroxyl- and carboxylic-acid-terminated SAMs on a mercury electrode, by using electrochemical techniques that operate at distinct time scales. Two limiting voltammetric behaviors are observed, consistent with a diffusion control of the redox process at mercaptophenol-coated electrodes and a kinetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 99 publications
(117 reference statements)
4
31
0
Order By: Relevance
“…8 as calibration plots [25,26] to determine the Cu 2+ concentration in solution and, as the sensitivity of the GCErThM is higher than that of the bare electrode, we could consider that the modified GCEr is acting as an amperometric sensor to determine the concentration of Cu 2+ ions in solution. But this sensing behaviour does not achieve a plateau [24,25], i.e, a limit of intensity vs. c cu (see the figure inset inside Fig. 8, which is the same plot but when the bulk Cu 2+ concentration range is increased until 20 mM).…”
Section: +mentioning
confidence: 83%
See 1 more Smart Citation
“…8 as calibration plots [25,26] to determine the Cu 2+ concentration in solution and, as the sensitivity of the GCErThM is higher than that of the bare electrode, we could consider that the modified GCEr is acting as an amperometric sensor to determine the concentration of Cu 2+ ions in solution. But this sensing behaviour does not achieve a plateau [24,25], i.e, a limit of intensity vs. c cu (see the figure inset inside Fig. 8, which is the same plot but when the bulk Cu 2+ concentration range is increased until 20 mM).…”
Section: +mentioning
confidence: 83%
“…But now the reaction Cu 2+ -ThM + 1 eCu 2+ (sln) (6) implies also the permeation across the ThM coating-solution interface. As the permeation seems to be a kinetically slow process [24], it is possible that some of the Cu 2+ formed in the reverse scan remains bonded to ThM molecules in the coating layer and permits the permeation equilibrium to be achieved faster when the bulk Cu 2+ concentration in solution is increased.…”
Section: +mentioning
confidence: 99%
“…Among their many uses, mercaptoalkanoic acid (MA) SAMs have been applied as biomimetic templates for inorganic crystal nucleation and growth [2,3], surface tethers for biologically active species [4,5] and platforms for cell culture [6]. The SAMs have also been successfully employed as components in biosensors and immunosensors [7,8,9,10] and show great promise in the development of molecular electronic devices [11]. In recent years, however, the isomers of mercaptobenzoic acid (MBA) have been identified as viable alternatives for preparing SAMs with carboxyl or carboxylate functionality [10,13,14,15,16,17,18,19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…According to most recent results, kinetically fast redox couple [Ru(NH3)6] 3+/2+ can detect the smallest ("unvisible" for other markers) defects in the SAM, that is a manifestation of the much more sensitive nature of the [Ru(NH3)6] 3+/2+ couple (higher demanding conditions) to the SAM defects, compared to other markers [20,[29][30][31][32]. The latter conclusion can be justified by the recent quantum-chemical calculations of charge distribution within the complex ions, which demonstrated that in the case of hexamine metal complexes the excess charge is located on the metal core in the ion center whereas, for example, in the case of hexacyano metal complexes on the terminal nitrogen atoms of cyano ligands [35].…”
Section: Resultsmentioning
confidence: 99%
“…This redox couple is known to be capable to penetrate into the SAM interior, disclosing tiny defects that "invisible" for other markers (for example to [Fe(CN) 6 ] 3-/4-, at otherwise similar conditions [13]), and show up through different kinetic patterns [28][29][30][31]. , operating at the SAM modified gold electrodes of different thickness, searching for the mechanism turnover from the adiabatic to nonadiabatic one, under the conditions when the redox probe can permeate into the SAMs' interior.…”
Section: Introductionmentioning
confidence: 99%